Boundary control : subnational authoritarianism in federal democracies - Gibson, Edward L. (Cambridge studies in comparative politics., 2012)
"This book explains how subnational authoritarianism is part of normal democratic politics and strategic interactions between local authoritarians and national democratic leaders"--